Kombinasi Imbuhan Herbal Kunyit dan Zink dalam Pakan sebagai Alternatif Pengobatan Kolibasilosis pada Ayam Pedaging (THE COMBINATION OF CURCUMIN WITH ZINC IN FEED AS ALTERNATIF THERAPY COLLIBACIILOSIS IN BROILER ) - Wientarsih, Ietje; Widhyari, Sus Derthi; Aryanti, Tika (Jurnal Veteriner, 2013)
The use of antibiotics is one way to reduce the number of deaths in poultry industry. However, use maybe reduced because the impact for consumers. This study aims to find out the effect of the combinationbetween herbal turmeric (Curcuma domestica Val.), Garlic (Allium sativum Linn.) with Zn in the feed tothe number of erythrocyte, hematocrit and hemoglobin in chickens that is infected with Escherichia colibactery. Two hundred head of DOC were divided into 5 treatments and 4 repetitions, each repetitionconsisted of 10 chickens. Ration treatment K0 (basal ration as a healthy chickens), K (negative control)(basal ration chickens infected with Escherichia coli), P1 (basal ration + 1.5% turmeric powder + 180 ppmof ZnO / chickens infected with Escherichia coli), P2 (basal ration + 2.5% garlic powder + 180 ppm of ZnO /chickens infected with Escherichia coli), and K (positive control) (a basal ration + antibiotic / chickensinfected with Escherichia coli). At the age of 3 weeks, all treatment groups were challenged with E. coliwhich treated  orally at a dose of 108 CFU/mL. K(+) group was given antibiotics a day after the challenge. Antibiotics are given for 3 days with a dose of medication. Blood sampling performed at the age of 3 weeks(before the challenge), 1 and 2 weeks after the challenge. The blood test includes the number of erythrocytes,hematocrit values and level of hemoglobin  . The results showed the number of erythrocytes, hematocritvalues, and level of hemoglobin at treatment P1 (ration basal + 1.5% turmeric powder + 180 ppm of ZnO+ infected with Escherichia coli) tend to be higher than other treatments and have equal outcomes withtreatment K(+) (ration basal + antibiotics + infected with Escherichia coli). From the results of this studyconcluded that the use of combinations of herbs turmeric and Zn in the feed can be used as an alternativeof colibacillosis treatment.
Keywords: erythrocyte, hematocrit, hemoglobin, E. coli, turmeric, garlic, zinc